The Role of Judges in Dealing with Community Development - Hasanudin, Maulana (Universitas Islam Negeri Walisongo Semarang, 2020)
The purpose of this paper is to determine the role of the judge in facing the development of society. Judges are part of the important structure of the judicial power branch in Indonesia. Judicial power is an independent power to administer justice in order to uphold law and justice. Judges are given the power to judge. Judges have an important role as law enforcement officers in the law enforcement process in Indonesia, so they must pay attention to legal objectives. The role of the judge has consequences for the responsibility of the judge which is very heavy, where the judge has responsibility to one God, to the nation and state, to himself, to the law, to the parties and to society. Judges and society are elements that cannot be separated in a legal system. The judge is a product of the society and culture where he comes from and is. The function of the judiciary is to decide disputes between individuals and individuals, individuals and communities, even individuals or society and the state; forming or making a policy or policy.[]Tujuan penulisan ini adalah mengetahui peranan peranan hakim dalam menghadapi perkembangan masyarakat. Hakim merupakan bagian dari struktur penting cabang kekuasaan kehakiman di Indonesia. Kekuasaan Kehakiman merupakan kekuasaan yang merdeka untuk menyelenggarakan peradilan guna menegakkan hukum dan keadilan. Hakim diberi wewenang untuk mengadili. Hakim memiliki peranan penting sebagai aparat penegak hukum dalam proses penegakan hukum di Indonesia, sehingga harus memperhatikan tujuan hukum. Peranan hakim memiliki konsekuensi terhadap pertanggungjawaban hakim yang sangat berat, dimana hakim memiliki tanggung jawab terhadap tuhan yang maha esa, terhadap bangsa dan negara, terhadap diri sendiri, terhadap hukum, terhadap para pihak dan terhadap mayarakat. Hakim dan masyarakat merupakan unsur yang tidak bisa dilepaskan dalam suatu sistem hukum. Hakim sebagai produk masyarakat dan budaya tempat dia berasal dan berada. Fungsi kehakiman adalah memutus sengketa antara individu dengan individu, individu dengan masyarakat, bahkan individu atau masyarakat dengan negara; membentuk atau membuat policy atau kebijakan.